Decomposing the Returns to Regional Mobility - Rebecca Fehn; Hanna Frings (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
This paper studies the returns to regional mobility based on a sample of job-to-job transitions in Germany. Additionally, we provide evidence for the selection mechanisms into regional mobility and sorting into firms and matches. Using linked employer-employee data we estimate a wage decomposition including individual, firm and match fixed effects. Our (preliminary) results suggest a wage level increase of 28% for regionally mobile individuals, whereas workers making a job-to-job transition in their local labor market region experience an increase of 24%. Further, workers generally experience a move to higher paying firms, whereas this effect is smallest for regionally mobile workers. In addition, workers find relatively better matches due to the job-to-job transition; with regionally mobile workers benefiting most form this increase in match quality.
Keywords: J31; J62; R23; 330; regional mobility; wage growth; job-to-job transitions; firm effects; match effects